2005
DOI: 10.1002/bip.20340
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of polyC–scleroglucan complexes

Abstract: Successive changes of solvent conditions can be used to dissociate and reassociate the triple-helical structure of (1,3)-beta-D-glucans. Ultramicroscopic techniques have revealed a blend of circular and other structures following renaturation. When this solvent exchange process is carried out in the presence of certain polynucleotides, the process creates a novel macromolecular complex. Here, we use size exclusion chromatography (SEC) to study such (1,3)-beta-D-glucan-polynucleotide complexes. Online multi-ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The formation of a complex between (1,3)‐β‐ D ‐glucans and certain polynucleotides88–92 opens for the use of (1,3)‐β‐ D ‐glucans as carriers for polynucleotides. The potential of (1,3)‐ β‐ D ‐glucan‐polynucleotide complexes for gene delivery purposes has also been reported93–95 and recently reviewed 24.…”
Section: The Ability Of (13)‐β‐d‐glucans To Interact With Various Stmentioning
confidence: 99%
“…The formation of a complex between (1,3)‐β‐ D ‐glucans and certain polynucleotides88–92 opens for the use of (1,3)‐β‐ D ‐glucans as carriers for polynucleotides. The potential of (1,3)‐ β‐ D ‐glucan‐polynucleotide complexes for gene delivery purposes has also been reported93–95 and recently reviewed 24.…”
Section: The Ability Of (13)‐β‐d‐glucans To Interact With Various Stmentioning
confidence: 99%
“…By combining the above analytical features, traditional SEC coupled with an inline MALS detector (SEC‐MALS) has been a popular choice for qualitative and semi‐quantitative product characterization in pharmaceutical, agricultural, and medical applications 29, 32–36. It has been applied to a variety of bio‐molecules including proteins,36 carbohydrates,37 polysaccharides,38 viral particles,39 and nucleotides 40. A primary advantage over traditional SEC is that SEC‐MALS provides absolute M w without the need of size calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Based on those publications, we explored whether the application of ultramicroscopy combined with multidetector chromatography could provide further information. Our result indicated that poly‐cytidylic acid (polyC) was included in the linear and not the macrocyclic structures of scleroglucan after renaturation . The l p s of polyC–scleroglucan complexes were exceeding that of the (1,3)‐β‐ d glucan triplex.…”
Section: Xanthan: An Example Of a Polysaccharide Adopting A Duplex Stmentioning
confidence: 80%